FGF13 interaction with SHCBP1 activates AKT-GSK3α/β signaling and promotes the proliferation of A549 cells. Issue 11 (1st November 2020) - Lu, Hongzhao; Yin, Meichen; Wang, Ling; Cheng, Jia; Cheng, Wei; An, Huanping; Zhang, Tao
ABSTRACT: FGF13, a member of the FGF subfamily, has been found to be highly expressed in cancer cells such as prostate cancer, melanoma, glioma and multiple myeloma. However, the mechanism of FGF13 function during cancer cell proliferation remains to be unexplored, especially Non-small cell lung cancer (NSCLC). In this study, the cell proliferation effect of FGF13 on A549 cells was checked by CCK-8, clone formation, Ki67 immunofluorescence staining and Flow Cytometry assay. Localization of FGF13 within A549 cells was performed with confocal laser scanning microscope. The protein variations and interaction were measured by western blotting and co-immunoprecipitation analysis. It showed that FGF13 was mainly distributed in the cytoplasm and exhibited a high expression level in A549 cells. High expression of FGF13 activated AKT-GSK3 signaling pathway, and inhibited the activity of p21 and p27. Thus, FGF13 enhanced the process of transition from G1 to S phase and promoted A549 cells proliferation. Furthermore, the interaction between FGF13 and SHCBP1 was confirmed. Meanwhile, FGF13 and SHCBP1 had a cooperative effect to accelerate the cell cycle progression, especially the ability to promote cell proliferation is significantly enhanced via protein interaction. Hence, we conclude that FGF13 played a positive regulation role during A549 cells proliferation. FGF13 interacted with SHCBP1 to facilitate cell cycle progression, providing new insights into deep understanding of non-small cell lung cancer mechanisms of proliferation and regulation function of FGF13.